Neural Correlates of Switching Attentional Focus during Finger Movements: An fMRI Study - Zimmermann, Kristin; Bischoff, Matthias; Lorey, Britta; Stark, Rudolf; Munzert, Jörn; Zentgraf, Karen (Frontiers in Psychology, 2012)
Research on motor-related attentional foci suggests that switching from an internal to an external focus of attention has advantageous effects on motor performance whereas switching from an external to an internal focus has disadvantageous effects. We used functional magnetic resonance imaging to investigate the neural correlates of switching the focus of attention. Two experimental groups were trained to apply one focus direction – internal or external – on a previously learned finger tapping sequence. Participants with an internal focus training were instructed to attend to their moving fingers; those with an external focus training were instructed to attend to the response buttons. In the first half of the experiment, participants performed with their trained focus, in the second half, they were unexpectedly asked to switch to the untrained attentional focus. Our data showed that the switch from a trained internal to an unfamiliar external focus of attention elicited increased activation of the left lateral premotor cortex. We propose that this activation can be linked to the role of the premotor cortex in action planning — probably indicating a facilitation effect on selectional motor processes. Switching from a trained external to an unfamiliar internal focus of attention revealed enhanced activation of the left primary somatosensory cortex and intraparietal lobule. We interpret these modulations as a result of the amplifying influence of afferent information on motor processing when asked to attend internally in a motor task after being trained with an external focus.